La montaña mágica - Mann, Thomas, 1875-1955; García Adánez, Isabel; Mann, Thomas, 1875-1955. (Barcelona, España ; Capital Federal, Buenos Aires, Argentina : Edhasa, 2012)
A vast intellectual drama of the forces that play upon modern man, The Magic Mountain is set in a sanitorium in the Swiss Alps--a community organized with exclusive reference to ill health, and a symbol of the diseased society of Europe before 1914.
ePub edition published in February 2013.
Online resource; title from PDF title page (Digitalia, viewed July 17, 2015)
Keywords: Sanatoriums -- Fiction; Germany -- Fiction; Electronic books